Lack of emergence of associations between selected maternal exposures and offspring blood pressure at age 15 years. Issue 4 (15th January 2013) - Leary, Sam D; Brion, Marie-Jo; Lawlor, Debbie A; Smith, George Davey; Ness, Andy R
Abstract : Background: A recent review found little evidence for substantial effects of modifiable maternal exposures on offspring blood pressure (BP), but this may have been because almost all the studies reported on BP in early and mid-childhood. Methods: This study uses data on 4723 mother–child pairs, collected as part of the Avon Longitudinal Study of Parents and Children, Bristol, England between 1991 and 1997; associations between three maternal variables (smoking during pregnancy, age at childbirth and prenatal diet) and offspring BP at approximately 15 years were assessed. Comparisons of maternal and paternal associations with offspring BP were carried out as a way of evaluating whether prenatal exposures exerted an influence through intrauterine effects. Results: The selected maternal exposures were not associated with offspring BP, after minimal or full adjustment for potential confounders. Maternal and paternal associations with offspring BP for each exposure were found to be similar. Conclusions: The findings of this study suggest that associations between the selected maternal exposures and offspring BP do not emerge with age up to adolescence.